Adsorption of nitrogen-containing compounds on hydroxylated α-quartz surfaces. Issue 62 (7th November 2019) - Tsendra, Oksana; Boese, A. Daniel; Isayev, Olexandr; Gorb, Leonid; Scott, Andrea Michalkova; Hill, Frances C.; Ilchenko, Mykola M.; Lobanov, Victor; Leszczynska, Danuta; Leszczynski, Jerzy
Abstract : Adsorption energies of different nitrogen-containing compounds on two hydroxylated (001) and (100) quartz surfaces are computed. Abstract : Adsorption energies of various nitrogen-containing compounds (specifically, 2, 4, 6-trinitrotoluene (TNT), 2, 4-dinitrotoluene (DNT), 2, 4-dinitroanisole (DNAn), and 3-nitro-1, 2, 4-triazole-5-one (NTO)) on the hydroxylated (001) and (100) α-quartz surfaces are computed. Different density functionals are utilized and both periodic as well as cluster approaches are applied. From the adsorption energies, partition coefficients on the considered α-quartz surfaces are derived. While TNT and DNT are preferably adsorbed on the (001) surface of α-quartz, NTO is rather located on both α-quartz surfaces.